Acute Myocardial Infarction in Scottish Military Veterans: A Retrospective Cohort Study of 57, 000 Veterans and 173, 000 Matched Nonveterans. Issue 12 (8th May 2014) - Bergman, Beverly P.; Mackay, Daniel F.; Pell, Jill P.
Abstract : Few studies of veterans have examined cardiovascular disease as the primary outcome, other than in relation to specific conflicts or hazards. To assess the long-term risk and prognosis of acute myocardial infarction (AMI) in United Kingdom veterans from a broad range of military backgrounds and experience, we conducted a retrospective cohort study of 57, 000 veterans resident in Scotland and 173, 000 civilians matched on age, sex, and area of residence. Cox proportional hazards models were used to compare the risks of fatal/nonfatal AMI overall, by sex, and by year of birth, adjusting for the potentially confounding effect of socioeconomic status, and to compare rates of case-fatality following AMI at 30-day, 1-year, and 5-year follow-up. Over a mean follow-up period of 29 years between 1981 and 2012, a total of 2, 106 (3.8%) veterans experienced an AMI as compared with 5, 261 (3.1%) nonveterans (hazard ratio = 1.22, 95% confidence interval: 1.16, 1.29; P < 0.001). There was an increased risk of AMI among veterans born in 1945–1959 but not among those born from 1960 onward. Case-fatality was lower among veterans at 30-day, 1-year, and 5-year follow-up. We conclude that health behaviors such as smoking may have increased the risk of AMI in older veterans but that younger veterans have benefited from in-service health promotion initiatives.